Preaching and culture - Dreyer, T. F. J. (HTS teologiese studies, 2005)
Before the new political dispensation in South Africa (1994), the Dutch Reformed Church in Africa (Nederduitsch Hervormde Kerk van Afrika) referred to the church as a “peoples church” (volkskerk). Owing to political changes the qualification “volkskerk” has created a certain degree of disturbance in the ranks of the church. The relationship between “church and culture” became a topical issue. Since 1994 the focus of the homiletical debate shifted to the question of the role of the church within a changing environment and again the answer to the question of “church and culture” was of utmost importance. Nowadays the reality of a multicultural society becomes a new challenge to the church. This article is an attempt to define the relation between culture and preaching from different hermeneutic perspectives, namely the cultural embedding of the biblical kerygma; the interwovenness of language and culture; and the necessity for contextuality in preaching.